The influence of cage density on growth and behavior of Tangerang-Wareng Pullets - Iskandar, Sofjan; Setyaningrum, S.D.; Amanda, Y.; Rahayu H.S, Iman (Indonesian Animal Sciences Society, 2009)
One hundred and eight pullets of 13 weeks old white Tangerang-Wareng, were allocated to numbers of wire cages. Each cage had 4050 cm2 floor space. The treatments were three cage-densities (4, 6 and 8 pullets/cage) with six replications for each treatment for growth observation, while there were other three treatments (observation times), which were 07.00-08.00 (morning), 12.00-13.00 (noon) or 17.00-18.00 (afternoon), that were applied and replicated in three for behavior observation. Commercial ration containing 20.86% crude protein, 3.22 Ca, 0.87% total P and 2982 kkal metabolizable energy (ME)/kg and drinking water were provided ad libitum. Results showed that cage density neither significantly (P<0.05) affected birdsâ final bodyweight, bodyweight gain, feed consumption nor feed conversion ratio. Analysis of variance showed that there was no interaction effect of cage densites and observation times on every observed behavior variable, except on standing activity. Cage density did not significantly (P<0,05) affect behavior, except behavior of cleanning, which increased with the increase of space allocation. The presentages of eating and pecking were significantly increase in the morning, while presentage of bird having a rest increased at noon. Drinking behavior was not affected by both cage density and observation time. The most birds showed the highest activities in the morning. In general the most cage density of 8 birds/4050 cm2 of floor space (506 cm2/bird), was more likely comfortable to the birds to live. Key words: Cage Density, Tangerang-Wareng Pullet, Growth, Behavior